Brain Metastasis as an Initial Manifestation of Ovarian Carcinoma: A Case Report - Zafer Selçuk Tuncer; Gokhan Boyraz; Aslıhan Yazıcıoğlu; İlker Selcuk; Senem Özge Yücel (Case Reports in Medicine)
Brain metastasis is a rare and late manifestation of ovarian carcinoma. A 30-year-old woman initially presenting with neurologic symptoms was later found to have mucinous ovarian carcinoma. The patient had a 6 cm adnexal mass with multiple millimetric brain metastatic lesions. Following a surgical staging laparotomy procedure, the patient received brain irradiation and systemic chemotherapy.